Effect of the seed layer on the growth and orientation of the ZnO nanowires: Consequence on structural and optical properties. (December 2017) - Serrano, A.; Arana, A.; Galdámez, A.; Dutt, A.; Monroy, B.M.; Güell, F.; Santana, G.
Abstract: High quality vertically aligned zinc oxide (ZnO) nanowires (NWs) were grown on Au-coated aluminum-doped zinc oxide (AZO) thin films via vapor-liquid-solid (VLS) technique. AZO seed layers were deposited using two different techniques named as ultrasonic spray pyrolysis (USP) and magnetron sputtering. Structural, morphological and compositional properties of the NWs grown on the two distinct seed layers were analyzed in detail by using X-ray diffraction (XRD), scanning electronic microscopy (SEM) and energy dispersive spectroscopy (EDS) techniques, respectively. In the first case, (seed layer grown by USP technology), NWs showed the (101) orientation, whereas in the second case, (seed layer grown by sputtering) NWs showed (002) orientation. It was confirmed by the SEM images, that NWs with (002) orientation shown better vertical alignment than NWs with (101) orientation. In addition, optical properties were also studied using photoluminescence (PL) spectroscopy and irrespective of the preferred orientation, NWs showed a strong green emission at room temperature. The study made in the present work on the seed layer preparation by two techniques and hence, deposition conditions to achieve fully controllable ZnO nanowires with precise distance, shape, position and orientation could provide opportunities for the fabrication of future optoelectronic devices. Highlights: ZnO seed layer was grown by ultrasonic-spray pyrolysis and magnetron sputtering. Physical, morphological and optical properties of the nanowires obtained from both of the seed layers have been studied. Green, bright emission is found to be due to the oxygen vacancies in the thin film.